If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1(15 + -12x) = -3(5 + -5x) 3x + (15 * -1 + -12x * -1) = -3(5 + -5x) 3x + (-15 + 12x) = -3(5 + -5x) Reorder the terms: -15 + 3x + 12x = -3(5 + -5x) Combine like terms: 3x + 12x = 15x -15 + 15x = -3(5 + -5x) -15 + 15x = (5 * -3 + -5x * -3) -15 + 15x = (-15 + 15x) Add '15' to each side of the equation. -15 + 15 + 15x = -15 + 15 + 15x Combine like terms: -15 + 15 = 0 0 + 15x = -15 + 15 + 15x 15x = -15 + 15 + 15x Combine like terms: -15 + 15 = 0 15x = 0 + 15x 15x = 15x Add '-15x' to each side of the equation. 15x + -15x = 15x + -15x Combine like terms: 15x + -15x = 0 0 = 15x + -15x Combine like terms: 15x + -15x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 24.8+(-8.7)-13= | | 4=1/4x | | m^10+7m^5+12=0 | | T(x)=-0.85x+9.6 | | 15(3-6)=56.25 | | (2+2)-(4*4)+(8-6)= | | 6x+9=7x+1 | | 22-5(6x-1)=63 | | 2(12-6x)=-3(9+4x) | | 8b-6b=18 | | 34+.5x=26 | | -2(5-n)=-7+5n | | 4(3x-5)=2x+90 | | 12x+54+12x+54= | | z^2-7=-18 | | N+(-4)=31 | | 7.5=(h+3)/2 | | K^2+9k-39=-k | | 7x-4(7x+6)=-192 | | t=7s-2 | | 81=1-5(x-8) | | 3x-6=-16 | | 0.25(20)+0.15x=0.10(20+x) | | 130x=48393 | | 3(m+3)-5=16 | | 1(x+2)-3(x-3)=5(2) | | 6xsquared+4x=0 | | 4v-5(8+6v)=-118 | | 10h=16 | | 8*x-3=40 | | 4c+9= | | 9x-84+85=5x+77 |